PD-1 inhibitors plus lenvatinib versus PD-1 inhibitors plus regorafenib in patients with advanced hepatocellular carcinoma after failure of sorafenib - Xu, Yongkang; Fu, Shumin; Shang, Kai; Zeng, Jiayu; Mao, Ye (Frontiers in Oncology, 2022)
Background: Lenvatinib、regorafenib and anti-programmed cell death protein-1 (PD-1) immunotherapy have shown promising clinical outcomes in patients with advanced hepatocellular carcinoma (HCC) after sorafenib failure, respectively. However, the combination of the two treatments has not been reported. We compared the efficacy of PD-1 inhibitors with lenvatinib (PL) and PD-1 inhibitors plus regorafenib (PR) in patients with advanced HCC in this study. Methods We conducted a retrospective study of advanced HCC patients who undergone PD-1 inhibitors combined with lenvatinib or regorafenib after failure of sorafenib at Second Affiliated Hospital of Nanchang University from July 2018 and December 2020. The overall survival (OS), progression-free survival (PFS), effective rates and treatment-related adverse events (TRAEs) were investigated. Results In total, 61 patients met the criteria and were included in the present study, and they were divided into the PL group (n = 32) and PR group (n = 29). The overall response rate (ORR) (12.5 %vs. 10.3%, respectively; p = 0.557) and disease control rate (DCR) (71.9%vs. 58.6%, respectively; p < 0.207) were higher in the PL group than in the PR group, but there was no statistical difference. Furthermore, median PFS and OS were not significantly different between the two groups in Kaplan-Meier survival analysis (PFS: 5.3 months vs 4.0 months, p = 0.512; OS: 14.1 months vs 13.7 months, p = 0.764 for the PL group vs PR group).The most common treatment-related adverse events (TRAEs) were hand -foot skin reaction (24/61,39.3%), hypertension (20/61,32.8%) and hypothyroidism (13/61,21.3%).The frequent TRAEs (≥Grade 3) during PD-1 inhibitors plus lenvatinib or regorafenib treatment were hand-foot skin reaction (5/29,12.4%), thrombocytopenia (2/29 6.90%) and proteinuria (n =2/32,6.25%). Conclusions Combination of lenvatinib/regorafenib and PD-1 inhibitors is a promising therapy for HCC patients after sorafenib failure. Keywords: PD-1 inhibitors, lenvatinib, regorafenib, sorafenib, hepatocellular carcinoma